Developing Knowledge of Supply Chain Resilience in Less-Developed Countries in the Pandemic Age - Lopes, João (2022)
Background: The constraints imposed by the pandemic COVID-19 increased the risks of the disruption of supply chains, bringing new challenges to companies. These effects were felt more intensely in less-developed countries, which are highly dependent on imports of products and raw materials. This study aims to assess the impact of supply chain resilience in a less-developed country (Guinea-Bissau) using complex adaptive system theory. Methods: We used a qualitative methodology through multiple case studies. Semi-structured interviews were conducted with four companies. The semi-structured script contains questions about supply chain disruptions, vulnerabilities and resilience. Results: The main results show that the companies in Guinea-Bissau, due to their dependence on the outside world and the absence of formal, larger and more diversified supply chains, suffered serious consequences with the disruption imposed by the pandemic. It was also concluded that the more resilient the supply chain, the fewer the impacts of crisis events and that the resilience of companies at this level depends on their obtaining competitive advantages over their competitors. Conclusions: The main practical implications of this study are the need to formalize the supply chain, diversify the supply of services and products of companies dependent on the exterior, adopt metrics that allow for the early detection of situations of supply chain disruption, effectively manage stocks and promote proactive crisis resolution strategies. Studies on the impact of resilience on supply chains in crises are scarce, especially on companies located in underdeveloped countries.